2006
DOI: 10.1111/j.1574-6968.2006.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the adhesion of PCC®Lactobacillus fermentumVRI 003 to Peyer's patches

Abstract: The characteristics of the adhesion of PCC Lactobacillus fermentum VRI 003 to Peyer's patches was studied in vitro. The adhesion of L. fermentum 003 was strongly inhibited in the presence of d-mannose and methyl-alpha-d-mannoside although other carbohydrates tested, such as N-acetyl-glucosamine, d-galactose, d-glucose and l-fucose, did not affect the adhesion. Lactobacillus fermentum 003 was shown to strongly attach to mannose immobilized on a surface using BSA, suggesting that L. fermentum 003 specifically ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A number of Lactobacillus species, including L. plantarum, L. salivarius, L. johnsonii, L. paracasei and L. fermentum, were previously shown to be able to express mannose-specific (MS) adhesins with the capacity to adhere to mannose-containing glycoproteins on epithelial cells Ahrne et al, 1998;Neeser et al, 2000;Kang and Conway, 2006). This was confirmed in the present study, and extended to include also L. gasseri, L. reuteri, L. acidophilus, L. vaginalis, L. parabuchneri, L. hilgardii, L. parafarraginis and L. brevis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of Lactobacillus species, including L. plantarum, L. salivarius, L. johnsonii, L. paracasei and L. fermentum, were previously shown to be able to express mannose-specific (MS) adhesins with the capacity to adhere to mannose-containing glycoproteins on epithelial cells Ahrne et al, 1998;Neeser et al, 2000;Kang and Conway, 2006). This was confirmed in the present study, and extended to include also L. gasseri, L. reuteri, L. acidophilus, L. vaginalis, L. parabuchneri, L. hilgardii, L. parafarraginis and L. brevis.…”
Section: Discussionmentioning
confidence: 99%
“…We have described an adhesin in L. plantarum that mediates adherence to mannose-containing receptors on colonic epithelial cells . Mannosespecific adhesins have subsequently been demonstrated in several species, including L. salivarius, L. johnsonii, L. paracasei and L. fermentum (Ahrne et al, 1998;Neeser et al, 2000;Kang and Conway, 2006), all members of the oral and/or faecal microbiota. Adherence to mannose-containing receptors is abolished or reduced in the presence of soluble mannose, and is hence termed mannosesensitive (MS) adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The competition for adhesion sites and production of antibiotic substances are considered the main mechanisms for probiotic effects of Lactobacillus against pathogens (Kesarcodi‐Watson et al ., ). Msa have been found in Lactobacillus plantarum , Lactobacillus salivarius , Lactobacillus johnsonii and Lactobacillus paracasei (Ahrne et al ., ; Neeser et al ., ; Pretzer et al ., ; Kang & Conway, ), suggesting that competition for mannose‐containing receptors in vivo between V. parahaemolyticus and certain strains of lactobacillus. Moreover, the in vitro inhibitory activity of Lactobacillus strains against Vibrio species including V. parahaemolyticus has been reported in a previous study (Koga et al ., ), and the results showed that V. parahaemolyticus was sensitive to a subset of the tested Lactobacillus strains.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important attribute of GRAS bacteria that could be exploited to replace antibiotic therapy for treating bacterial vaginosis gut infections and peptic ulcers. Adhesive capacity and colonization of the gastrointestinal tract of humans and animals by probiotic lactobacilli including L. fermentum have been extensively investigated [3941]. Organism can be delivered at the site of action, that is, gut or vagina, in the lyophilized capsular form where it can multiply and establish itself.…”
Section: Discussionmentioning
confidence: 99%